Services marketing : - Lovelock, Christopher (Pearson, 2011)
Organized around a strategic marketing framework Services Marketing provides instructors with maximum flexibility in teaching while guiding students into the consumer and competitive environments in services marketing. The marketing framework has been restructured for this edition to reflect what is happening in services marketing today.